Trypanosoma rangeli displays a clonal population structure, revealing a subdivision of KP1(−) strains and the ancestry of the Amazonian group. Issue 4 (March 2015) - Sincero, Thaís Cristine Marques; Stoco, Patricia Hermes; Steindel, Mário; Vallejo, Gustavo Adolfo; Grisard, Edmundo Carlos
Graphical abstract: Highlights: Population structure analysis supports the clonal structure of Trypnosoma rangeli and the KP1(+) and KP1(−) groups. Single -nucleotide polymorphism (SNP) and microsatellite analyses suggest three T. rangeli groups: Amazonian, KP1(−) and KP1(+). The newly proposed Amazonian group is related to Rhodnius brethesi . Abstract: Assessment of the genetic variability and population structure of Trypanosoma rangeli, a non-pathogenic American trypanosome, was carried out through microsatellite and single-nucleotide polymorphism analyses. Two approaches were used for microsatellite typing: data mining in expressed sequence tag /open reading frame expressed sequence tags libraries and PCR-based Isolation of Microsatellite Arrays from genomic libraries. All microsatellites found were evaluated for their abundance, frequency and usefulness as markers. Genotyping of T. rangeli strains and clones was performed for 18 loci amplified by PCR from expressed sequence tag/open reading frame expressed sequence tags libraries. The presence of single-nucleotide polymorphisms in the nuclear, multi-copy, spliced leader gene was assessed in 18 T. rangeli strains, and the results show that T. rangeli has a predominantly clonal population structure, allowing a robust phylogenetic analysis. Microsatellite typing revealed a subdivision of the KP1(−) genetic group, which may be influenced by geographical location and/or by the co-evolution of parasite and vectors occurring within the same geographical areas. The hypothesis of parasite–vector co-evolution was corroborated by single-nucleotide polymorphism analysis of the spliced leader gene. Taken together, the results suggest three T. rangeli groups: (i) the T. rangeli Amazonian group; (ii) the T. rangeli KP1(−) group; and (iii) the T. rangeli KP1(+) group. The latter two groups possibly evolved from the Amazonian group to produce KP1(+) and KP1(−) strains.